An unusual new species of Pentaneura Philippi (Diptera: Chironomidae) from northeastern Brazil, with an emended diagnosis to the genus - Dantas, Galileu P.s.; Pinheiro, Marcos P. G.; Hamada, Neusa (Zootaxa, 2020)
Pentaneura herbeti sp. nov. is described and illustrated based on male, female, pupa and larva collected in Northeastern region of Brazil. In addition, an amendment in the adult, pupal and larval diagnosis of Pentaneura is provided.